Dietary ferulic acid improves growth performance of broilers via enhanced intestinal antioxidant capacity and barrier function - Yaodong Hu; Shi Tang; Wei Zhao; Silu Wang; Caiyun Sun; Binlong Chen; Yuxing Zhu (Animal Bioscience)
Objective In this study, the effects of dietary ferulic acid (FA) on the growth traits, antioxidant capacity, and intestinal barrier function of broilers were investigated. Methods In total, 192 male Arbor Acres broilers were randomly allocated to one of three dietary groups (8 replicates of 8 birds each): control (CON) group (basal diet), FA100 group (basal diet + 100 mg/kg FA), or FA200 group (basal diet + 200 mg/kg FA). The duration of the feeding trial was 42 days. Results Higher average daily gain (ADG) and lower feed to gain (F/G) ratio during day 0 to day 21 were found in the FA100 and FA200 groups, while higher ADG and lower F/G during day 21 to day 42 were only found in FA200 group, compared to the CON group (p<0.05). Serum levels of malondialdehyde and diamine oxidase on day 21 were lower in the FA100 and FA200 groups and those on day 42 were lower in the FA200 group, while glutathione peroxidase level in the FA100 and FA200 groups on day 21 and that in the FA200 group on day 42 were increased (p<0.05). On day 21, jejunal glutathione synthetase (GSS) expression was upregulated in the FA200 group (p<0.05), while jejunal and ileal expression of nuclear factor erythroid 2-related factor 2 (NRF2) and Occludin as well as ileal expression of glutathione peroxidase 1 (GPX1) and zonula occludens 1 (ZO1) were increased in the FA100 and FA200 groups compared to the CON group (p<0.05). On day 42, mRNA expression of GSS, NRF2, SOD1, and GPX1 in the jejunum and ileum as well as Claudin2 in the jejunum and Occludin in the ileum were increased in the FA200 group (p<0.05). Conclusion Dietary FA addition could improve the growth performance, antioxidant capacity, and gut integrity of broilers. The current findings provided evidence that the adoption of FA can be a nutrition intervention measure to achieve high-efficient broiler production for poultry farmers.